ANALISIS SPASIAL TEMPORAL SEBARAN HUTAN MANGROVE MENGGUNAKAN CITRA LANDSAT 8 - Muhammad Dzaky Naufal Winaz; Defwaldi Defwaldi; Fajrin Fajrin; Dwi Marsiska Driptufanny (Cross-border, 2023)
Mangroves are tropical coastal plants or vegetation that live in large and open coastal areas. Mangroves are found mainly in tropical climates. Mangroves function as guard lines, reduce wind energy, and as a habitat or place to live for other biota such as fish, shrimp, molluscs, and crabs. Many factors affect the survival and growth of mangroves, including mangroves usually grow well in moist and muddy habitats and are influenced by tides. Mangrove habitat has several special properties or characteristics including salinity, tides, wind, and muddy substrate. These factors help mangroves in the growth and survival of mangroves. Mangroves usually grow well on soil or sand substrates with a fine texture like mud and rich in humus and sulfides (Thangam & Kathiresan, 1990). The method used in this study is the Maximum Classification method which is clipped with the NDVI results that have been Reclassified. The results of this study show that the change in mangrove forests in 2014 to 2018 increased by 40.101 hectares, the area of mangrove forests in 2018-2020 decreased by 755.269 hectares, in 2020-2022 it increased by 122.38 hectares. This area is known from the distribution of mangrove forests which is then clipped with NDVI which has been reclassified to get Mangrove Density.